2020
DOI: 10.1038/s41598-020-73767-w
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting from dawn to sunset for four consecutive weeks induces anticancer serum proteome response and improves metabolic syndrome

Abstract: Metabolic syndrome is characterized by central obesity, insulin resistance, elevated blood pressure, and dyslipidemia. Metabolic syndrome is a significant risk factor for several common cancers (e.g., liver, colorectal, breast, pancreas). Pharmacologic treatments used for the components of the metabolic syndrome appear to be insufficient to control cancer development in subjects with metabolic syndrome. Murine models showed that cancer has the slowest progression when there is no food consumption during the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 77 publications
(108 reference statements)
1
58
0
Order By: Relevance
“…After obtaining approval from the Institutional Review Board of the Baylor College of Medicine (Protocol number H-31612) and informed consent from all subjects, we conducted pilot studies in subjects with metabolic syndrome and healthy subjects who observed the month of Ramadan in 2019 and 2018, respectively [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After obtaining approval from the Institutional Review Board of the Baylor College of Medicine (Protocol number H-31612) and informed consent from all subjects, we conducted pilot studies in subjects with metabolic syndrome and healthy subjects who observed the month of Ramadan in 2019 and 2018, respectively [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported the inclusion and exclusion criteria for both studies [ 16 , 17 ]. Briefly, for the study conducted on subjects with metabolic syndrome, we included those who were 18 years of age or older, agreed to have a FibroScan® [ 18 ] and planned to fast during the month of Ramadan [17] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations